Photoluminescence of Metal–Polymer Complexes Based on Functional Triazole–Carbazole Copolymers with Terbium Ions - Ruslan Smyslov; Artem Emel’yanov; Tatiana Nekrasova; Galina Prozorova; Svetlana Korzhova; Olga Trofimova; Alexander Pozdnyakov (Applied Sciences, 2023)
Functional copolymers of 1-vinyl-1,2,4-triazole (VT) and N-vinylcarbazole (VK) were synthesized using a free-radical polymerization. The content of hole-conducting N-vinylcarbazole units was found to be 9, 16, and 37 mol. %. Fourier transform infrared spectroscopy, 1H-NMR spectroscopy, gel permeation chromatography, thermogravimetric analysis, and differential scanning were applied to characterize the poly(VT–co–VK). Based on a polymer ligand, metal−polymer complexes with Tb3⁺ ions were obtained in a polymethyl methacrylate matrix, and their luminescent properties were studied. The maximum photoluminescence of the complex can be achieved when using 16 mol. % of N-vinylcarbazole units. This is because two photoprocesses (excimer formation and excitation energy transfer) occur simultaneously and competitively.